This preview shows page 1. Sign up to view the full content.
Unformatted text preview: -x 2 ( t ) y 1 ( t )) = ( a + d ) m ( t ) . Solve this ﬁrst order diﬀerential equation like you were taught in MAP2302, and you get m ( t ) = e ( a + d ) t m (0) . 4. x ( t ) = X ( t ) c, X ( t ) = ± e-t e 2 t 3 e 2 t ² , c = ± e-2 3 e-3 2 3 e-2 ² * Instructor: Patrick De Leenheer....
View Full Document
This note was uploaded on 04/07/2008 for the course MAP 4305 taught by Professor Deleenheer during the Spring '06 term at University of Florida.
- Spring '06